Identifying physiological traits to optimize assimilate partitioning and spike fertility for yield potential in wheat (Triticum aestivum L.) genotypes - Rivera-Amado, Alma Carolina (2016)
Although wheat demand is expected to increase along with a projected growing population, the global rate of wheat yield increase appears to be declining. Genetic progress in yield potential in the past has been achieved mainly through increases in grains m-2 and harvest index with no major changes in above-ground biomass; however, HI has not increased since about 1990 indicating that further increases in yield potential will rely on increases in biomass while optimizing grain DM partitioning. A panel of 26 high biomass CIMMYT elite spring wheat cultivars (CIMMYT Mexico Core Germplasm; CIMCOG) was evaluated for grain yield, above-ground dry-matter (AGDM), DM partitioning and spike fertility in three field experiments (2011, 2012 and 2013) in NW Mexico. An additional field experiment was carried out in 2014 on a subset of four cultivars to examine source-sink related traits by imposing source manipulation treatments (leaf-lamina removal and leaf-sheath shading) on the crop. The main objective was to identify the physiological determinants of grains m-2 and HI in relation to DM partitioning among organs and to prioritise traits for application in breeding to increase HI in high biomass genotypes. Genetic variation in grain yield among genotypes was explained mainly by differences in AGDM. Fruiting efficiency (grains per unit spike DM at anthesis) was affected by high rachis specific weight and appeared to be important in grains m-2 determination. Trends for positive associations were observed between HI and spike partitioning index (Spike DM / AGDM - at anthesis; SPI). Stem DM proportion (mainly structural DM in internodes 2 and 3) was negatively associated with SPI; peduncle length and peduncle DM as a proportion of the stem DM on the other hand were more strongly associated to spike DM per unit area. In 2014, reductions in final grain weight in response to source reduction treatments were relatively low compared to the estimated reductions in light interception. No up-regulation of photosynthesis rate was observed by the flag-leaf or the spike in response to source reductions, suggesting that grain growth was overall sink limited but close to a co-limitation by source and sink. These results indicated scope for designing a plant ideotype to raise HI in high biomass spring wheat cultivars with reductions in stem structural DM (in upper internodes) without major effects on water soluble carbohydrate accumulation (in lower internodes). Finally, results from the source-sink manipulation treatments indicated limited scope for reductions in leaf-sheath and lamina DM partitioning during stem elongation to favour spike growth.